Stroke occurrence by hypertension treatment status in Ghana and Nigeria: A case-control study - Akpalu, A.; Sarfo, F.S.; Asowata, O.J. (Journal of the Neurological Sciences, 2024)
Background: Hypertension is preeminent among the vascular risk factors for stroke occurrence. The wide gaps in awareness, detection, treatment, and control rates of hypertension are fueling an epidemic of stroke in sub Saharan Africa. Purpose: To quantify the contribution of untreated, treated but uncontrolled, and controlled hypertension to stroke occurrence in Ghana and Nigeria.
Research Article
Keywords: Stroke; Hypertension; Prevention